God's image and global cultures : integrating faith and culture in the twenty-first century - Nehrbass, Kenneth (Eugene, Oregon : Cascade Books, an imprint of Wipf and Stock Publishers, 2016)
Globalization has raised numerous questions about theology and culture for Christians. How should we respond to outsourcing and immigration? How does anti-Western sentiment affect the proclamation of the gospel? What is the role of the church in society? This book argues that Christians will be most fulfilled and most effective if they embrace their cultural activity rather than feel ambivalent about it. The central question of this book is, how does bearing God's image relate to cultural activity? Nehrbass explains that "spheres of culture," such as political, technological, and social structures, are systems that God has instilled in humans as his image bearers, so that they can glorify and enjoy him forever. Therefore, a theology of culture involves recognizing that the kingdom of God encompasses heaven and Earth, rather than pitting heaven against Earth. The text surveys anthropological explanations for humanity's dependence on culture, and shows that each explanation provides only partial explanatory scope. The most satisfying explanation is that a major functional aspect of bearing God's image is engaging in culture, since the Trinity has been eternally engaged in cultural functions like ruling, communicating, and creating. Each chapter contains a summary and questions about what it means to be a world-changer in the twenty-first century. --
The gospel and global trends -- Understanding culture and theology -- God's thoughts about culture -- Competencies for cross-cultural impact.
Includes bibliographical references (pages 219-229).
Print version record.
Master record variable field(s) change: 650
Keywords: Christianity and culture; Multiculturalism -- Religious aspects -- Christianity; Culture; Globalization -- Religious aspects -- Christianity; Culture and globalization; Image of God; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Christianity and culture; Culture; Culture and globalization; Globalization -- Religious aspects -- Christianity; Image of God; Multiculturalism -- Religious aspects -- Christianity; Electronic books